Empowering Women Through Microfinance - Anand , Gurleen Kaur; Srivastava, Ankita (International Journal of Psychosocial Rehabilitation, 2020)
–The microfinance programme in its different forms such as micro-credit, micro-insurance etc is constantly working for upgrading the economic situation of women. The fundamental idea behind this is to empower and encourage women to become financially independent and take their own decisions. This in turn is likely to increase self-respect and self-confidence of women participants. The present paper aims at identifying that whether microfinance helps in the development of women in India. A sample of 500 participants through ordered probit regression revealed the positive impact of the micro-funding on empowerment.